2022
DOI: 10.1136/bmjopen-2022-062147
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing receipt of an antibiotic prescription among insured patients in Tanzania: a cross-sectional study

Abstract: ObjectivesThere are limited data on factors influencing antibiotic prescription among insured patients. We assessed for correlates of an antibiotic prescription among insured patients.DesignA cross-sectional study.SettingThe study was conducted at the National Health Insurance Fund offices, Dar es Salaam, Tanzania.Data sourceWe captured data from the claim forms, containing inpatient and outpatient treatment information for insured patients, for the month of September 2019.Outcome variableReceipt of an antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 9 Another study focusing on prescribing antibiotics to insured patients in Dar es Salaam reported that penicillins were the most preferred group of antibiotics, followed by nitroimidazoles. 32 The findings are further different from what was observed in tertiary care hospitals in India, where cephalosporins 37 and β-lactam antibiotics 27 were the most frequently prescribed antibiotics. Also in Pakistan, where cephalosporins were the most commonly prescribed class of antibiotics, followed by penicillins and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 9 Another study focusing on prescribing antibiotics to insured patients in Dar es Salaam reported that penicillins were the most preferred group of antibiotics, followed by nitroimidazoles. 32 The findings are further different from what was observed in tertiary care hospitals in India, where cephalosporins 37 and β-lactam antibiotics 27 were the most frequently prescribed antibiotics. Also in Pakistan, where cephalosporins were the most commonly prescribed class of antibiotics, followed by penicillins and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 60%
“… 31 For example, despite the fact that viral diseases such as colds and flu cannot be treated with antibiotics, patients are nonetheless given antibiotic prescriptions for such disorders. 32 …”
Section: Discussionmentioning
confidence: 99%
“…The findings in this study highlight considerable issues and concerns regarding the current prescribing practices of antibiotics across the sectors, which can include the excessive prescription of 'Watch' antibiotics in private care settings [74,116,134,137,139]. However, encouragingly, this is generally not the case in Tanzania, with import data showing that 83.1% of imported antibiotics in recent years are from the 'Access' group versus only 10.1% from the 'Watch' group and <0.01% from the 'Reserve' group [27].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, there has been a general overprovision of care, including unnecessary prescriptions of antibiotics [98,138]. Of equal concern is the high rate of prescribing of antibiotics from the 'Watch' list seen in some studies, which reached up to 33.3% of antibiotics prescribed in one study [98,139]. Having said this, Mbwasi et al (2020) found that >90% of all antimicrobial consumption in Tanzania, based on import data, was 'Access' as opposed to 'Watch' and 'Reserve' antibiotics, with the most utilization in the private versus public sectors [28].…”
Section: Prescription Of Antibiotics In Private Ambulatory Care Facil...mentioning
confidence: 99%
See 1 more Smart Citation